Potentiality of shallow brown sand aquifers as an alternative safe drinking water source in Bengal Basin - Biswas, A.; Bhattacharya, P.; Halder, D.; Jacks, G.; Nath, B.; Mukherjee, Abhijit; Kundu, A.; Mandal, U.; Chatterjee, D. (2012)
The present study investigated the regional distribution of brown sand aquifers (BSA) as well as their hydrogeochemical contrast to grey sand aquifers (GSA). The data indicated that in BSA redox status is limited to the Mn oxides reduction stage, while in GSA, Fe oxides reduction to SO 4 2 - reduction processes are prevalent. Though, the concentration of dissolved As was very low ( < 10 µg/L) in BSA, the concentration of Mn was very high ( > 400 µg/L). Whereas in GSA, the enrichment patterns of As and Mn were opposite to that of BSA. This study suggests that underlying health risk of Mn in drinking water needs to be addressed more rigorously before advocating for mass scale exploitation of BSA as an alternative drinking water source despite of significantly low As concentration in groundwater. © 2012 Taylor & Francis Group.